Molecular basis of early stages of Clostridium difficile infection: germination and colonization. (August 2012) - Sarker, Mahfuzur R; Paredes-Sabja, Daniel
Clostridium difficile infections (CDIs) occur when antibiotic therapy disrupts the gastrointestinal flora, favoring infected C. difficile spores to germinate, outgrow, colonize and produce toxins. During CDI, C. difficile vegetative cells initiate the process of sporulation allowing a fraction of the spores to remain adhered to the intestinal surfaces. These spores, which are unaffected by antibiotic therapy commonly used for CDIs, then germinate, outgrow and recolonize the host's GI tract causing relapse of CDI. Consequently, the germination and colonization processes can be considered as the earliest and most essential steps for the development as well as relapse of CDI. The aim of this review is to provide an overview on the molecular basis involved in C. difficile spore germination and colonization.